Assessment of small-scale landslide treatment in Nepal - Mathema, P; Joshi, J (Banko Janakari, 2010)
Landslides are major natural hazards in Nepal, and efforts are underway to treat smallscale landslides with people's participation. The main purpose of this study was to assess various aspects of the prevalent practice of landslide treatment followed by the Department of Soil Conservation and Watershed Management, Government of Nepal. Questionnaire survey and case study methods were used to collect the necessary information. It appears that the landslide treatment has been successful in stabilizing the major portion of the treated landslides. However, landuse improvement above the treated landslides, and drainage management inside and around the treated landslide sites were found to be inadequate. Also, the maintenance of constructed structures and vegetation was not satisfactory. The findings and recommendations of this paper will be useful in improving the landslide treatment in Nepal. Keywords: Drainage management; landslide treatment; landuse improvement; people's participation DOI: 10.3126/banko.v20i1.3502 Banko Janakari, Vol. 20, No. 1 pp.3-8